4-Bromo-4'-chloro pyrazoline analog of curcumin augmented anticancer activity against human cervical cancer, HeLa cells: in silico-guided analysis, synthesis, and in vitro cytotoxicity. Issue 5 (23rd March 2020) - Chaudhary, Monika; Kumar, Neeraj; Baldi, Ashish; Chandra, Ramesh; Babu, M. Arockia; Madan, Jitender
Abstract: Inspired by the synergistic effects of hetero-aromatic scaffolds on curcumin, a novel array of pyrazoline substituted curcumin analogs was designed. Multi-scale computational studies were carried out to target the proposed analogs on human kinase β (IKK-β), a potential anti-cancer target. In molecular docking analysis, all the eleven molecules were observed to bind the target site and 4-bromo-4'-chloro analog displayed three hydrogen bond interactions with a docking score of –11.534 kcal/mol higher than parent molecule, curcumin (docking score = –7.12 kcal/mol) as the propellant shaped of analogs aided in proper binding with Kinase Domain binding pocket. The molecular dynamics and simulations studies revealed that the stable complexes of lead molecule were developed as the minimal deviations per residue of protein found within the range of 0.11 to 0.92 Å. The proposed compounds were synthesized, characterized and biologically evaluated against human cervical cancer cell line, HeLa, using standard MTT cell assay. Bio-evaluation studies exhibited superior cytotoxic profile for many analogs as Chloro bromo analog with IC50 value (8.7 µg/mL) exhibited fivefolds improvement in the potency in comparison to curcumin (IC50 = 42.4 µg/mL) but was less potent than the standard drug, paclitaxel (IC50 = 0.008µg/mL). The apoptotic effect was evaluated in the terms of caspase-3 enzyme cleavage and exhibited 70.5% of apoptosis significantly ( p  < 0.05) higher than 19.9% induced by curcumin. In short, 4-bromo-4'-chloro analog was the potent cytotoxic agent in this structural class and must be evaluated further under a set of stringent parameters for transforming in to a clinically viable therapeutic molecule. Communicated by Ramaswamy H. Sarma